Influence of running phases on the postural balance of modern pentathlon athletes in a laser run event - Sadowska, D.; Lichota, M.; Sacewicz, T.; Krzepota, J. (International Journal of Environmental Research and Public Health, 2019)
Background: The Laser Run combined event is part of the modern pentathlon, consisting of successive shooting and running phases. The main factor hindering accurate and fast shooting is the increasing fatigue caused by running effort. The aim of this study was to assess the impact of the running phases on the postural balance in the shooting position of pentathletes in a Laser Run event. Methods: 25 modern pentathletes (18.6 ± 1.7 years), members of the Polish Association of Modern Pentathlon, completed a Laser Run event. During each shooting series, a Zebris dynamometric platform recorded the displacement of the centre of pressure (COP). Results: Significant changes in the average velocity of the COP (F = 3.43; p = 0.0223) and the width of the ellipse of the COP shifts area WoE (F = 3.30; p = 0.0259) between the first and the second shooting series were observed. The average velocity of the COP in series I was 72.6 m/s and increased to 84.3 m/s in series II. In turn, the average width of the ellipse of the COP in series I reached 29.1 mm and in series II, 34.1 mm. Conclusions: The fatigue caused by the running phases in the Laser Run affects the stability of the shooting position of pentathletes. Disturbances that occur after the first running phase are maintained at the same level during the subsequent shooting series. The fatigue level does not affect the magnitude of the disturbances of the postural balance in the shooting position.